SISTEM INVENTORY SUKU CADANG BERBASIS CLIENT-SERVER PADA CV. SARANA MANDIRI MOTOR - Riyan Naufal Hay’s; Eva Safaah; Agi Febrian Ramadhan (Universitas PGRI Yogyakarta, 2019)
Sarana Mandiri Motor was established in 2006 which is engaged in four-wheeled vehicle maintenance services, the provision of administrative services for spare parts and transaction receipts is still recorded on a sheet of paper (form) and stored on the map. This results in the processing of data into information needed by the administrative section not to work properly. Therefore, an e-inventory parts system would be built that will be applied in the CV. Sarana Mandiri Motor. This system development method uses a prototype method, system design using UML (Unified Modeling Language). While the database application development tools use MYSQL and the Borland Delphi programming language. This system will be integrated using the Client-Server network so that it can simplify admin and warehouse performance in processing and monitoring CV. Sarana Mandiri Motor. Keywords: Inventory System, Parts, Prototype, Client-Server.